Teaching for purpose preparing students for lives of meaning - Malin, Heather (Cambridge, Massachusetts Harvard Education Press, 2018)
This book highlights for educators the role that purpose plays in youth development and in motivating students to develop cognitive as well noncognitive skills that teachers are seeking to instill.--Provided by publisher
Part I. Purpose and education - 1. What is your purpose? -- 2. Play, meaning and intention -- 3. Purpose and social and emotional learning -- 4. The three dimensions of purpose -- Part II. Purpose in school and in the classroom -- 5. Purposeful schools -- 6. Profiles: Quaglia institute and the Future Project -- 7. Purposeful instruction -- 8. Profiles: noble impact and project wayfinder -- 9. Purposeful curricula -- 10. Profiles: open future institute and mosaic -- 11. Creating a place for purpose.
Includes bibliographical references and index.
Keywords: Affective education -- United States; Social learning -- United States; Educational psychology -- United States; Education -- Aims and objectives -- United States; Educational change -- United States; Education, Humanistic -- United States